Brucella abortus ornithine lipids are dispensable outer membrane components devoid of a marked pathogen-associated molecular pattern - Palacios-Chaves, Leyre (2011)
The brucellae are a-Proteobacteria facultative intracellular parasites that cause an important zoonosis. These bacteria escape early detection by innate immunity, an ability associated to the absence of marked pathogen-associated molecular patterns in the cell envelope lipopolysaccharide, lipoproteins and flagellin. We show here that, in contrast to the outer membrane ornithine lipids (OL) of other Gram negative bacteria, Brucella abortus OL lack a marked pathogen-associated molecular pattern activity. We identified two OL genes (olsB and olsA) and by generating the corresponding mutants found that olsB deficient B. abortus did not synthesize OL or their lyso-OL precursors. Liposomes constructed with B. abortus OL did not trigger IL-6 or TNF-a release by macrophages whereas those constructed with Bordetella pertussis OL and the olsB mutant lipids as carriers were highly active. The OL deficiency in the olsB mutant did not promote proinflammatory responses or generated attenuation in mice. In addition, OL deficiency did not increase sensitivity to polymyxins, normal serum or complement consumption, or alter the permeability to antibiotics and dyes. Taken together, these observations indicate that OL have become dispensable in the extant brucellae and are consistent within the trend observed in a-Proteobacteria animal pathogens to reduce and eventually eliminate the envelope components susceptible of recognition by innate immunity.